Desain Buku Interaktif Digital Tentang Stunting untuk Anak-anak Di Indonesia - Putriyanti, Rany; Wibowo, Yudi (Universitas Sahid Surakarta, 2025)
Stunting is a major child health problem in Indonesia due to chronic malnutrition. Low consumption of nutritious food and children's limited understanding of healthy eating patterns are factors that require special attention. Early education is a crucial step in developing children's understanding of balanced nutrition and instilling healthy lifestyle habits. This study aims to design a digital interactive book as a stunting education medium for children aged 5-9 years. The ADDIE (Analysis, Design, Development, Implementation, Evaluation) method was used, including needs analysis, media design, interactive content development, trial implementation, and evaluation of media effectiveness. The results show that the digital interactive book is effective in conveying messages about the importance of balanced nutrition and the role of a healthy diet in preventing stunting. However, its limitation is the need for parental guidance in understanding certain interactive content and features for optimal learning. Therefore, the interactive book is an innovative alternative educational medium in efforts to prevent stunting, with parental involvement still needed to support the success of nutrition education for children. Keywords : Stunting, Balanced Nutrition, Children's Education, Digital Interactive Book, ADDIE Method